Benefit in regionalisation of care for patients treated with radical cystectomy: a nationwide inpatient sample analysis. (5th September 2013) - Ravi, Praful; Bianchi, Marco; Hansen, Jens; Trinh, Quoc‐Dien; Tian, Zhe; Meskawi, Malek; Abdollah, Firas; Briganti, Alberto; Shariat, Shahrokh F.; Perrotte, Paul; Montorsi, Francesco; Karakiewicz, Pierre I.; et al.
Abstract : Objective: To quantify in absolute terms the potential benefit of regionalisation of care from low‐ to high‐volume hospitals. Patients and Methods: Patients with a primary diagnosis of bladder cancer treated with radical cystectomy (RC) were identified within the Nationwide Inpatient Sample, a retrospective observational population‐based cohort of the USA, between 1998 and 2009. Intraoperative and postoperative complications, blood transfusions, prolonged length of stay, and in‐hospital mortality rates represented the outcomes of interest. Potentially avoidable outcomes were calculated by subtracting predicted rates (i.e. estimated outcomes if care was delivered at a high‐volume hospital) from observed rates (i.e. actual observed outcomes after care delivered at a low‐volume hospital). Multivariable logistic regression models and number needed to treat were generated. Results: Patients treated at high‐volume hospitals had lower odds of complications during hospitalisation than those treated in low‐volume hospitals. Potentially avoidable intraoperative complications, postoperative complications, blood transfusions, prolonged hospitalisation, and in‐hospital mortality rates were 0.6, 7.4, 2.8, 9.4, and 2.0%, respectively. This corresponds to a number needed to redirect from low‐ to high‐volume hospitals in order to avoid one adverse event of 166, 14, 36, 11 and 50, respectively. Conclusion: This is the first report to quantify the potential benefit of regionalisation of RC for muscle‐invasive bladder cancer to high‐volume hospitals.